2017
DOI: 10.1186/s13256-017-1302-7
|View full text |Cite
|
Sign up to set email alerts
|

St John’s wort (Hypericum perforatum)-induced psychosis: a case report

Abstract: BackgroundSt John’s wort (Hypericum perforatum) has been known for centuries for its therapeutic properties and its efficacy as an antidepressant has been confirmed by a growing body of evidence. During the last two decades it has also come to prominence with a wider public, due to advertising efforts across Europe and United States of America. However, its availability without prescription, as an over-the-counter medication, raises some concern regarding its clinical management and unsupervised administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
4
1
2
Order By: Relevance
“…Unlike our results, case studies by Ferrara et al 30 and Arold et al 31 did not find SJW to be a perfectly safe and convincing alternative. They reported risks associated with its use, and suggested checking its dose and side effects more carefully before using it in the treatment of depression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our results, case studies by Ferrara et al 30 and Arold et al 31 did not find SJW to be a perfectly safe and convincing alternative. They reported risks associated with its use, and suggested checking its dose and side effects more carefully before using it in the treatment of depression.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the evidence regarding St. John's wort efficacy for the treatment of depression with fewer adverse effects is still insufficient since many studies, like the case study by Ferrara et al 30 and Arold et al, 31 did not find it perfectly safe and reported risk associated with its use in the treatment of depression. The contradictions regarding St. John's wort's safety and efficacy arise due to the limited amount of available case reports, use of unblinded assessments, and lack of refined analysis and evidence-level grade assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The suspected product contained H. perforatum aerial parts (hypericin 0.3%) and R. rosea root (rosavin 3%). Several cases (n = 14) of psychotic symptoms associated with H. perforatum administration have been published, although a past psychiatric history of mental disorder was usually present (Bostock, Kirkby, Garry, Taylor, & Hawrelak, 2018;Ferrara, Mungai, & Starace, 2017). Regarding R. rosea, one case of restlessness and trembling has been reported but with the concomitant assumption of the SSRI paroxetine (Maniscalco, Toffol, Giupponi, & Conca, 2015).…”
Section: Central Nervous System Reactionsmentioning
confidence: 99%
“…Однако, препараты H. perforatum имеют бóльшую частоту возникновения специфических побочных эффектов, включая реакции со стороны нервной и репродуктивной систем, органов слуха и зрения, печени и почек [28]. Сообщается о развитии психоза у пациента, принимавшего настой H. perforatum без назначения врача [29].…”
Section: результаты и обсуждение антидепрессивная активностьunclassified